PENGARUH LATIHAN UPHILL DAN DOWNHILL RUNNING TERHADAP POWER TUNGKAI SISWA SSB ARTAJUSI LAMPUNG UTARA - Muhammad Yopan Antono; Reza Adhi Nugroho (Journal of Physical Education, 2022)
This study aims to determine the effect of Uphill and Downhill Running exercises on the leg power of SSB Artajusi North Lampung students.This study uses an experimental method with a "one group pretest - posttest design". The population in this study were students of SSB Artajusi North Lampung with a sample of 24 men. Sampling in this study was carried out by purposive sampling, with the criteria (1) students who are still actively participating in training at SSB Artajusi North Lampung, (2) male, (3) students under 17 years old / U-17 , (4) able to follow the planned exercise program from start to finish, (5) not in a state of illness. Based on these categories, the sample was given a leg power pretest using a standing broad jump test instrument.The results of this study indicate that (1) There is a significant effect of Uphill and Downhill Running exercises on the leg power of SSB Artajusi North Lampung students. (2) From the results of the t-test, it can be observed that the t-count is greater than the t-table (12.758 1.713) and a significant value of p is (0.000 0.05), this result explains that there is a significant difference between the pretest and posttest of Uphill and Downhill Running exercises. Against Leg Power of SSB Artajusi Students, North Lampung. The average pretest data is 75.92 while the posttest is 81.21 with an increase of 5.29.